Student Well-Being in The VARK-Based PjBL Model for Biology Learning - Rahmi, Annisa Salsyabila; Rahmat, Adi; Priyandoko, Didik (Bioscientist : Jurnal Ilmiah Biologi, 2024)
This study aims to analyze the effect of the Project-Based Learning (PjBL) model, adapted to the VARK learning styles, on student well-being in biology learning, particularly in the context of digestive system material. The research used a quantitative quasi-experimental design with control and experimental groups. Results indicated that the average Student Well-Being score for the control group was 48.3%, while for the experimental group, it reached 51.7%. These findings highlight that implementing the VARK-based PjBL model can improve student well-being and contribute to better learning outcomes by accommodating diverse learning styles and reducing learning-related anxiety. Furthermore, the model promotes collaborative learning and meaningful engagement, leading to a more supportive and enjoyable educational experience. The study recommends the adoption of innovative teaching methods that prioritize student well-being and engagement to create a more effective and enjoyable learning environment.